Pemerolehan Bahasa Kedua Aspek Fonologi Anak Usia 4-5 Tahun di Toraja - Jamaluddin Gesrianto A'ban; Muhammad Darwis; Nurhayati Nurhayati (Universitas Negeri Makassar, 2022)
Abstract. The purpose of this study is to explain the second language acquisition of the phonological aspects of children aged 4-5 years in Toraja. The researcher uses a psycholinguistic approach as a scalpel by focusing on the speech of the second language of children aged 4-5 years on the phonological aspect by focusing on the pronunciation of phonemes. The results showed that at the phonological level, there was a change in the consonant phoneme /r/ to /l/ and a change in the vowel phoneme /e/ to /a/, as well as a change in the vowel phoneme /ə/ into /e/. The phoneme omission is found in the phoneme /h/ which is at the beginning of the word and at the end of the word, as well as the omission of the vowel phoneme /e/. The omission of syllables is found in the first syllable in a word consisting of three or more syllables. Based on the research data, it can be concluded that the second language acquisition of the phonological aspects of children aged 4-5 years in Toraja is dominantly influenced by the first language in the form of phonological interference of letter changes.Keywords: Second Language Acquisition, Psycholinguistics, Toraja Children's Speech